Exploring the extent of digitalisation and digital diplomacy in Pakistan embassies. Issue 2 (3rd July 2022) - Habibullah,; Xiguang, Li
ABSTRACT: This study examines Pakistan embassies' social media adoption, use, and level of public engagement in relation to 'networked public diplomacy'. Web surveying showed that majority of the embassies have accounts on social networking sites, but some are inactive. The manual content and thematic analysis of tweets ( n = 490) collected during December 2019 from the Twitter accounts of five Pakistan embassies revealed considerable differences in the number, regularity and frequency of the posts; but showed similarity in the message content disseminated by the embassies. The results also demonstrated that the embassies generally follow state-centric informative and one-way communication strategies, with the exception of one embassy that somewhat engaged its audience through Twiplomacy. A key finding showed that embassies in places with fewer diaspora are more effective in producing messages that encourage dialogic communication compared with embassies with a larger expat population. In addition, results from user profile analysis of the accounts' followers suggested a limited digital presence of Pakistani missions among the foreign netizens. In general, the findings showed that Pakistan embassies are present on social media sites, but lack the inclination to communicate dialogically in real time and to show reasonable presence among digital audiences.